Thank you for your service - Terima kasih atas khidmat tuan: Educating citizens to express appreciation to our armed forces personnel - Abdullah Adnan, Mohamed; Nur Syafawati, Sabuan (UMPSA, 2024)
The attainment of a nation's independence from colonial rule typically stemmed from an enduring struggle fuelled by widespread patriotism. These efforts to secure independence resulted in the establishment of military forces dedicated to preserving the nation's liberty against any potential threats. In the years of the post-independence era, patriotism is woven into a nation's identity via the sacrifices of its military services. Every day, men and women wear uniforms, ready to face the unknown, serve, and defend. Their passion for duty is unshakable and unrivalled. However, within their valour lurks a modest gesture that is sometimes overlooked: a genuine "thank you for your service."